A human rights analysis of informed consent to psychotropic medication : significance for protecting the sexual rights of women living with depression in Nigeria - Ngwena, Charles (University of Pretoria, 2025)
Mini Dissertation (MPhil (Sexual and Reproductive Rights in Africa))--University of Pretoria, 2024.